Comparison of the integrated organ/systems-based curriculum with the traditional subjects-based medical curriculum: Short communication - Obi, Clinton Onyebuchi; Onosogbe, Moses; Ehimen, Asemota Gift; Olamide, Omotoye; Toluwalase, Titilola Victor; Esther, Ovbiagele; Joshua, Dawodu Oluwananumi; Aborode, Abdullahi Tunde (Annals of medicine and surgery, 2022)
Medical education has undergone numerous reforms within the last century. Such reforms have produced numerous models of curricula across the world, which includes but is not limited to organ systems-based, problem based and traditional discipline based medical curricula. The system based of medical education in Nigeria need reform as different system are subjective to different effects on students performance and mental health. This article discuss two curricular models and identify their relative strengths and weaknesses; especially in a country like Nigeria.